Udin: Optimalisasi Capacity Development UMKM Melalui Strategi Digital Marketing di Masa Pandemi Covid-19 - Dita Ratnasari; Dyah Ayu Wiranti; Alivia Rachma M. (EXERO : Journal of Research in Business and Economics, 2021)
Every year the growth of Micro-Small and Medium Enterprises (MSME) has increased by 4.2% from 2016-2019 with a contribution to GDP of 50%. However, there is a challenge in the future: declining turnover due to high consumer interest through digital transactions, while only 13% of MSMEs are connected to the go-digital network. Whereas the concept of digital marketing provides hope for MSMEs to develop into centers of economic power. Departing from these problems, the author has the innovation called Udin (UMKM Digital Marketing), which is a platform that allows the empowerment of MSMEs through a digital-based creative economy in an effort to optimize capacity development. Udin will be integrated with the Department of Industry, Cooperatives and MSMEs. The methodology used is descriptive qualitative with literature study. The existence of innovation is expected to be able to regenerate go-digital-based MSMEs through capacity building in digital marketing, the impact of which is correlated to the improvement of the national economy as well as an effort to increase the standard of living of a just and prosperous society.